Methodological Approaches to Determining the Monopolisation Level of Primary Residential Real Estate Regional Markets in Ukraine - Pavlov, Kostiantyn V.; Павлов, Костянтин Володимирович (National University “Lviv Polytechnic”, 2018)
In this article the author investigates the typology and main characteristics of the markets and provides the definition of the concept of "competition". Several methodological approaches were suggested in order to determine the magnitude of the monopolisation level of primary residential real estate regional markets as well as the market share belonging to a certain construction company. The aims of these approaches are: to determine the concentration level in the market – the scale of the largest enterprises "threshold market share"; to analyse the state of the competitive environment – "The Index of market concentration"; the Linda index; "The Herfindahl-Hirschman Index"; "The Lerner Index"; "The Dispersion Index"; "The Entropy Index"; "The Lorentz curve"; The Gini coefficient.
Keywords: competition definition methodology; real estate market monopolisation; developers competition; residential real estate; housing; primary market; market share of construction; housing construction